2012, No. 11, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting and practiceJonas Žaptorius, Sustainability accounting: a brief history and concept, 7Kristina Rudžionienė, Erika Krakauskaitė, Fair value measurement in accounting, 18Akvilė Stulpinaitė, Judita Biveinytė, The comparative analysis of the 12th Business Accounting Standard and International Accounting Standards regulating accounting of tangible long-term assets, 28Jonas Mackevičius, Jokūbas Leipus, Peculiarities of Muslim banks’ accounting, 40Martynas Novikovas, Transfer pricing control and audit in Lithuania, 51Management accounting and practiceLina Veličkienė, Kristina Rudžionienė, Rūta Klimaitienė, Job – costing method in small service companies, 66Lionius Gaižauskas, Budgets preparing and application problems in the Lithuanian enterprises, 76Svetlana Vegera, Accounting of environmental and social land rent in modern system of economic relations: problems and principles of methodology, 91Financial analysis and evaluationRamunė Budrionytė, Laimutė Kazlauskienė, Rasa Subačienė, System of ratio analysis of tourism companies, 98Gerda Venckevičiūtė, Gražina Jatuliavičienė, Performance measurement systems development: from financial to corporate perspective, 116Stasys Valentinavičius, The theoretical aspects of evaluation company’s investment preference, 127
Keywords: none